Necessity as a driver in bending agricultural gender norms in the Eastern Gangetic Plains of South Asia - Timsina, Pragya; Chaudhary, Anjana; Sharma, Akriti; Karki, Emma; Suri, Bhavya; Brown, Brendan (International Maize and Wheat Improvement Center, 2023)
The majority of farmers in the rural global South continue to rely on agriculture for a living, either directly or indirectly. Despite accounting for nearly half of the world’s farmers, women face gender-specific challenges such as deeply ingrained cultural and social norms that limit their access to land, assets, financial markets, agricultural training, and information. This study investigates how necessity is becoming one of the major drivers in the bending of agricultural gender norms, using semi-structured interviews with farmers in the Eastern Gangetic Plains. As a result of labor shortages, the absence of male household members due to emigration, or their involvement in other lucrative income-generating livelihood activities, we discovered that women’s roles and participation in agriculture are adjusted on a needs basis. Women’s involvement in agriculture was not motivated by a willingness or desire to work in agriculture, but rather by a necessity arising from their financial situation. Thus, this study focuses on the growing trend of bending gender norms, and makes recommendations for increasing women’s participation and scope in future agriculture development initiatives through gender-equitable policies and interventions.